Influence of Cutaneous Involvement in Deciding how to Treat Psoriatic Arthritis. Issue 3 (September 2014) - Gusis, Simon Eduardo; Montoya, Sandra Fabiana; Castelli, Andrea; Mario, Kerzberg Eduardo; Kogan, Nora Noemi; Veira, Rosana Cyntia
Background: Cutaneous psoriasis precedes joint disease in 84% of patients with psoriatic arthritis. We believe that skin involvement should be considered when deciding how to treat psoriatic arthritis. Objective: The goal of our study was to investigate how the severity of skin disease influenced the management of psoriatic arthritis. Methods: Fifty patients with psoriatic arthritis and cutaneous involvement were studied. The severity of joint and skin involvement was evaluated. Treatment decisions for each patient were based on the most severe presentation between skin and joint involvement. Results: Treatment decisions were guided and were compared by the most severe skin involvement in 22/50 patients (44%), by the most severe joint involvement in 16 patients (32%), and by both skin and joint involvement in 12 patients (24%). There were no statistically significant differences (p <0.472). Conclusion: Treatment decisions in patients with psoriatic arthritis should be made in conjunction with decisions about skin treatment.